From Scratch to Plate: “Accounting Information Systems for Spices In Madura Island” - Citra Nurhayati; Nurul Kompyurini; Anita Carolina; Prayudi S Prabowo (Green Publisher Indonesia, 2022)
Spices are a priceless wealth of Indonesia. Many other countries in the world import it especially Europeans who desperately need pepper for almost all the flavors of its cuisine. The culinary history of Indonesia is not spared from the raw ingredients of spices that become the main raw materials of Indonesian specialties. Almost all the flavors of cuisine throughout Indonesia use spices as seasoning